Comparison Between Maximum Likelihood and Maximum Entropy Estimation Methods for Reliability of IDAL Distribution - Hamad, Alaa M.; Alkanani , Iden H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
IDAL distribution is based on expanding the exponential Weibull distribution by adding a IDAL distribution is based on expanding the exponential Weibull distribution by adding a third parameter, which is a shape parameter, to the exponential-Weibull distribution. This modification was done in order to create models that are more flexible and realistic. The IDAL distribution is characterized by three parameters, which are the scale parameter and two shape parameters. Estimating the reliability for a Noval distribution. The unknown parameters of its distribution have been estimated which have the first of these methods is the Maximum Likelihood Estimate (MLE) method, followed by the Maximum Entropy Estimation (MEE) method. A comparison of the outcomes and results of the applied methods has been carried out through data analysis and computer simulation between the estimating methods based on the applicable indicator mean square error (MSE) to investigate which way is the most effective. Additionally, the data that were observed have been displayed through the use of the MATLAB software package